THE INVESTIGATION OF THE ENGLISH EDUCATION STUDY PROGRAM STUDENTS’ MOTIVATION TREND IN LEARNING ENGLISH - Rivana, .; Salam, Urai; ., Wardah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2016)
Abstrak: Tujuan dari penelitian ini adalah untuk menggambarkan kecenderungan motivasi mahasiswa-mahasiswa dalam belajar bahasa Inggris di kelas. Penelitian ini dilaksanakan menggunakan metode deskripsi. Peneliti menggunakan daftar pertanyaan dan wawancara sebagai alat-alat pengumpul data. Data penelitian ini diambil dari mahasiswa-mahasiswa Program Studi Bahasa Inggris semester dua, empat dan enam tahun 2011/2012. Hasil penelitian menunjukkan bahwa mahasiswa-mahasiswa semester dua, empat dan enam mempunyai pola motivasi yang kurang lebih sama. Terdapat juga tujuh faktor-faktor yang berpengaruh terhadap motivasi para mahasiswa dalam belajar bahasa Inggris, yaitu: goals, needs, interest and coriosity, attitude, expectancy and self efficacy, lecturers as the role model, course content and classroom, dan social identity. Kata Kunci: Motivasi, kecenderungan motivasi Abstract:This research entitled The Investigation of The English Education Study Program Students’ Motivation Trend in Learning English. The purpose of this research is to describe students’ motivation trend in learning English in the classroom. This research was done in descriptive study. The researcher used questionnaire and interview as the tools of collecting data. The research data are taken from 2nd, 4th, and 6th semester students of English Education Study Program year 2011/2012. The research finding showed that 2nd, 4th, and 6th semester students have more or less same patterns of motivation. There are also seven factors that contribute to students motivation in learning English, they are: goals, needs, interest and coriosity, attitude, expectancy and self efficacy, lecturers as the role model, course content and classroom, and social identity. Keywords: Motivation, Motivation Trend